2021
DOI: 10.1155/2021/9947656
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin Attenuates Pathological Cardiac Remodeling after Myocardial Infarction via Activating PPARγ and PGC1α

Abstract: Rationale. Pathological cardiac remodeling serves as a vital mechanism during the progression from myocardial infarction (MI) to chronic heart failure (CHF). Nobiletin (NOB), an active monomer extracted from the peel of citrus fruit, has been reported to have beneficial effects in cardiovascular diseases. Our study was aimed at describing the specific mechanisms through which NOB protects against pathological cardiac remodeling after MI. Materials and Methods. C57BL/6 mice were treated with coronary artery lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Furthermore, our results showed that hesperidin, nobiletin and tangeretin could preserve cardiac systolic function after MI and activate PPARγ (Figure S5A, B). Besides, one of our previous studies suggested that nobiletin attenuated pathological cardiac remodelling after MI via activating PPARγ, 50 which is identical to our findings here. As to tangeretin, several studies indicated that it played an important role in lipid metabolism by increasing PPARγ expression 51,52 .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our results showed that hesperidin, nobiletin and tangeretin could preserve cardiac systolic function after MI and activate PPARγ (Figure S5A, B). Besides, one of our previous studies suggested that nobiletin attenuated pathological cardiac remodelling after MI via activating PPARγ, 50 which is identical to our findings here. As to tangeretin, several studies indicated that it played an important role in lipid metabolism by increasing PPARγ expression 51,52 .…”
Section: Discussionsupporting
confidence: 92%
“…Cui et al ( 19 ) have confirmed that pathological cardiac hypertrophy could be alleviated by reducing oxidation, inflammation, and apoptosis induced by AngII via Sirt1-mediated activation of AMPK/PGC1α signal molecules. Zhou et al ( 20 ) have found that nobiletin could attenuate post-myocardial infarction pathological cardiac remodeling via upregulating PGC1α. Besides, several new HF drugs exert their function via activating PGC1α.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of identified DECRs was validated further in clinical samples by RT-qPCR. RNA isolation and RT-qPCR were undertaken as described previously ( Zhou et al, 2021 ). In brief, red blood cell (RBC) lysis buffer (catalog number: C3702; Beyotime Institute of Biotechnology, Shanghai, China) was used to split RBCs.…”
Section: Methodsmentioning
confidence: 99%